Adventism and Minahasan Culinary Identity - Rumbay, Christar Arstilo (AL-ADYAN, 2021)
The debate between the culture and religion in Minahasa invites attention. The culture considers the existence of religion as a threat and potentially could destroy indigenous cultural identity. On the flip side, the religion regards cultural activities as an ancient legacy that bears no significance to theological worldview and modern civilization. Adventism, a Protestant denomination that shares extra attention to food doctrine, performs inhospitality toward Minahasan culinary identity. Engagement to consuming animal’s flesh, and even extreme food such as pork, rat, bat, dog, cat, spices ingredients, cap tikus, and related festivals that involves potluck, however, against Adventist teaching. Therefore, this essay conducts exploration to grasp how Adventism teaching could perform hospitality toward Minahasan culinary identity. This research occupies a qualitative approach and equips journals, books, and other references to contribute to the tension. In conclusion, Adventism should define the culture as a social bonding and expression of Minahasa. Minahasan culinary identity is not a theological or religious concern; instead, it should be defined as a sociology reflection. By doing so, Adventism will able to perform hospitality toward the culture.